Water replenishment through agricultural water conservation: an economic analysis of deficit irrigation - Sidwell, Jenny, author; Pritchett, James, advisor; Goemans, Christopher, advisor; Andales, Allan, committee member (Colorado State University. Libraries, 2013)
Available freshwater supplies are under growing pressure due to climate variability and expanding development. Water-intensive companies are becoming increasingly aware of the importance of managing their water use due to the impact it has, both on corporate profitability and local ecosystems. Many corporations have calculated the water footprint of their products to determine where reductions might be made. Water neutrality is an extension of a water footprint audit, and involves a consumer or producer reducing their water use as much as possible and then using additional measures to offset any remaining water use. Those additional measures include working with other water users to reduce their water use. For instance, a third party could contract with an agricultural producer and pay them reduce their own water use and then lease a portion of their water right. The objective of this thesis is to determine whether agricultural water conservation can be used to offset a business's residual water use, and more specifically, whether deficit irrigation can be a profit-maximizing option for that conservation. To that end, an optimization model was created and run in Excel's Solver using data from a USDA deficit irrigation research farm to estimate crop water production functions. The results of the model illustrate a range of profit maximizing crop mixtures and indicate potential lease quantities given a range of crop prices and lease payments.
Keywords: deficit irrigation; water neutral